2017
DOI: 10.1016/j.psyneuen.2016.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent binge alcohol exposure increases risk assessment behaviors in male Wistar rats after exposure to an acute psychological stressor in adulthood

Abstract: Teenage binge drinking is a common practice that has been shown to increase the risk for developing mood disorders in adulthood. The hypothalamo-pituitary-adrenal (HPA) axis is often dysfunctional in mood disorder patients, and animal models of adolescent binge alcohol exposure similarly show disordered HPA axis function, even after long periods of alcohol abstinence. Here, we sought to investigate the anxiety-like behavioral consequences of binge alcohol exposure in a Wistar rat model. Male rats were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Partly consistent with human research, cognitive studies in male rodents have shown that adolescent alcohol use predicts poorer executive functioning in adulthood, including cognitive flexibility (92,93), set shifting (94), and extinction of responses following termination of reinforcer cues (94)(95)(96). Adolescent alcohol use in male rodents has also been associated with poorer inhibition, reflecting heightened impulsivity and risk taking in adulthood (94,95,(97)(98)(99)(100). Similar to human studies, moderate alcohol use and binge drinking in male and female rodents predicts alterations in learning and memory during adolescence (101)(102)(103), however this may have minimal effects on later learning and memory in adulthood (104,105).…”
Section: Comparable Cross-species Findingsmentioning
confidence: 71%
“…Partly consistent with human research, cognitive studies in male rodents have shown that adolescent alcohol use predicts poorer executive functioning in adulthood, including cognitive flexibility (92,93), set shifting (94), and extinction of responses following termination of reinforcer cues (94)(95)(96). Adolescent alcohol use in male rodents has also been associated with poorer inhibition, reflecting heightened impulsivity and risk taking in adulthood (94,95,(97)(98)(99)(100). Similar to human studies, moderate alcohol use and binge drinking in male and female rodents predicts alterations in learning and memory during adolescence (101)(102)(103), however this may have minimal effects on later learning and memory in adulthood (104,105).…”
Section: Comparable Cross-species Findingsmentioning
confidence: 71%
“…However, Torcaso et al (2017), exposing male Wistar rats IG to ethanol (3 g/kg, P37-44) reported no behavioral changes on the EPM, whereas other researchers have demonstrated that adolescent ethanol exposure resulted in decreases of anxiety-like behavior on the EPM (Gilpin et al, 2012;Gass et al, 2014). For example, Long-Evans male rats were intermittently exposed to ethanol via VI during early-mid adolescence (P28-P42), and this exposure regimen resulted in decreased anxiety, as indexed by increased open arm behavior evident in adult rats (Gass et al, 2014).…”
Section: Adolescent Alcohol Exposure: Anxiety-like Behavioral Alteratmentioning
confidence: 99%
“…Animal models have been used to examine the long-term effects of adolescent alcohol use and have found interesting, yet somewhat inconclusive, results regarding negative affect and reward-related behaviors. Some research has shown increased adult voluntary drinking and anxiety-like behavior following adolescent ethanol exposure (Alaux-Cantin et al, 2013;Pandey, Sakharkar, Tang, & Zhang, 2015;Sakharkar et al, 2019), whereas others have identified decreases or no changes in these behaviors (Gass et al, 2014;Nentwig, Starr, Chandler, & Glover, 2019;Torcaso, Asimes, Meagher, & Pak, 2017). Of the few preclinical studies that have looked at the effects of low to moderate levels of intoxication, some results appear to be relatively consistent with the higher-level exposures, showing increased voluntary drinking in adulthood (Amodeo, Kneiber, Wills, & Ehlers, 2017;Broadwater, Varlinskaya, & Spear, 2013).…”
Section: Introductionmentioning
confidence: 99%